Emotional Abuse and Mental Health of Women in Abusive Marriage in Communities in Gwagwalada, Federal Capital Territory, Nigeria: Pelecehan Emosional dan Kesehatan Mental Wanita dalam Penganiayaan Pernikahan pada Komunitas di Gwagwalada, Wilayah Ibu Kota Federal, Nigeria - Victoria Ogwa Adikwu; John Johnson Edache; Mary Eru Iji; Egom Njin Ogar (Yayasan Ahmar Cendekia Indonesia, 2021)
The study specifically examines the impact of emotional abuse on the mental health of women in abusive marriages in communities in Gwagwalada, Federal Capital Territory, Nigeria. In order to achieve the objective of this study, the cross-sectional research method was adopted for the study. Data or the study was collected from a sample of 600 married women in Gwagwalada aged 18 and above using a self-structured questionnaire. The stratified and purposive sampling technique was used in selecting the sample from the study area. From the 600-instrument distributed only 594 was return without missing items or mutilation and this was used for analysis. Data collected from the field was analyzed using descriptive statistics such as tables, simple percentage and figure. The correlation analysis was carried using Pearson Product Moment correlation Analysis. Findings revealed that 95.2 per cent (566) of the sample in one time or the other in their marriage have suffered one form of emotional abuse, result also revealed that 93.8 percent of the respondents suffer psychologically as a result of emotional abuse from their spouse. The correlational analysis also revealed a strong significant relationship between emotional abuse and mental health issue among married women. The study therefore concludes that emotional abuse affects the mental health of married women in communities in Gwagwalada, Federal Capital Territory, Nigeria. the study therefore calls for increase in support service for those in abuse relationship. Abstrak Studi tersebut secara khusus meneliti dampak pelecehan emosional pada kesehatan mental wanita dalam pernikahan yang